Length-weight relationship and stock assessment of tuna fish (Euthynnus affinis) in East Halmahera waters - Hamid Taher; Syahnul Sardi Titaheluw; Aisyah Bafagih (Sekolah Tinggi Ilmu Pertanian Wuna, 2018)
The study was conducted in December 2016 to February 2017 in East Halmahera waters with the aim to examine the relationship between the length of weight and potential and the level of utilization of tuna. The results showed that the long frequency distribution of tuna was ranging from 10.0-28.2 cm, with a maximum length value of 29.93 cm, a growth coefficient of 0.74 per month and a measure of fish worth catching for spawning. The relationship between the weight of tuna in East Halmahera waters is W=0.0078L3.2982, where the length of tuna is greater than this weight increase due to environmental conditions and oceanographic parameters that affect the growth of tuna. The results of the MSY analysis or the sustainable resource potential of tuna in East Halmahera waters using the Fox method, found that the MSY value or sustainable potential of tuna was 4,176.54, with a maximum effort level of 8,047 Trips. This utilization rate is still low from the value of MSY and continues to decline this is due to the low value of fishing efforts.